ChemInform Abstract: Diastereoselective Photodimerization Reactions of Chromone‐2‐carboxamides to Construct a C2‐Chiral Scaffold. Issue 16 (April 2015) - Yagishita, Fumitoshi; Baba, Nozomi; Ueda, Yuki; Katabira, Satoshi; Kasashima, Yoshio; Mino, Takashi; Sakamoto, Masami
Abstract Irradiation of chromone‐carboxamides bearing a chiral auxiliary, e.g. (I), results in diastereoselective formation of a C2‐chiral anti‐HH dimer scaffold.